Flowering Intensity and Sex Ratio of Ber (Ziziphus mauritiana Lamk.) - Adhikary, T.; Kundu, S.; Chattopadhayay, P.; Ghosh, B. (International Journal of Bio-resource and Stress Management, 2019)
The field investigation was carried out at Horticultural Research Station, Mondouri, North 24 Parganas, B.C.K.V., West Bengal, India during 2015-16 with an objective to understand and provide a wealth of usable information of ber flowering and sex ratio in relation to ber breeding programme. Plant breeders look for ideal plant types or ideotypes in order to combine maximum desirable traits in a cultivar. For efficient and purposeful breeding programme, it is necessary to have knowledge of the floral morphology and biology of the parents. Keeping this in view, the experiment was laid out by Randomized block design (RBD) with three replication and fourteen varieties (Apple Kul, Banarasi Karaka, BAU-1 Kul, Chhuhara, Dandan, Gola, Illaichi, Jogia, Kaithali, Madhavpur, Mundia, Sanur-2, Topa and Umran). There was an appreciable variation of cyme emergence (1st August – 23rd August), number of flowers cyme-1 (11.2-34.6), number of cymes branchlet-1 (8.9-21.4) and number of flowers branchlet-1 (99.8-739.9). The variation of hermaphrodite flowers was remarkable both in early flowering season (4.1-38.7%) and peak flowering season (24.9-90.8%). In general, percentage of hermaphrodite flowers was more with a low sex ratio (male: hermaphrodite) in Umran, Illaichi, Gola, Sanur-2, Banarasi Karaka and Jogia variety. All the varieties showed wide variation of fruit set (3.9 to 31.4%). Further fruit set percentage is directly correlated with the sex ratio. This study provides the basis for understanding the floral biology, thus expanding the prospects for Z. mauritiana breeding programs and for further molecular and genetic studies of this species.